Greenland, view of Kjerulf Fjord through to Dicksons Fjord - Boyd, Louise Arner, 1887-1972 (1931)
August 2, 1931. Kjerulfs [Kjerulf] Fjord. Through to Dickson [Dicksons] Fjord. Right Valley, general direction east and west. In background on right is eastern terminal of range of mountains on the north side of Left Valley. In foreground Left Valley. Photo taken from eastern side of Left Valley, looking W.N.W.